Interoperability as a strategic focus in digital diversification and innovation A (Revista Científica Compendium, 2025)
The present study aims to discuss interoperability as a fundamental strategic axis in the processes of diversification and digital innovation within business management. In a context of technological acceleration, complex digital ecosystems, and high market volatility, diversification is consolidated as an essential strategy for growth and resilience, while digital innovation demands the reconfiguration of operational capabilities. Methodologically, a systematic review of recent specialized literature (2020-2025) was conducted, focused on the conceptual convergence between business strategy and information technologies. It is argued that interoperability should not be seen solely as a technical necessity for the integration of systems, processes, and actors, but rather as a true strategic support that acts as an enabling condition for operating efficiently on multiple fronts. The findings show that interoperability drives diversification by facilitating productive synergies and the efficient leveraging of the company's core competencies. By consolidating a shared and coherent data and process infrastructure, the creation of new products and business models is accelerated. In conclusion, the strategic adoption of interoperability is crucial for developing sustainable competitive advantages, ensuring more efficient and adaptable management, and positioning the company as a key player in the interconnected ecosystems of digital societies.
Keywords: interoperability; business diversification; digital innovation; strategic management